Evidence of Au(II) and Au(0) States in Bovine Serum Albumin-Au Nanoclusters Revealed by CW-EPR/LEPR and Peculiarities in HR-TEM/STEM Imaging - Radek Ostruszka; Giorgio Zoppellaro; Ondřej Tomanec; Dominik Pinkas; Vlada Filimonenko; Karolína Šišková (Nanomaterials, 2022)
Bovine serum albumin-embedded Au nanoclusters (BSA-AuNCs) are thoroughly probed by continuous wave electron paramagnetic resonance (CW-EPR), light-induced EPR (LEPR), and sequences of microscopic investigations performed via high-resolution transmission electron microscopy (HR-TEM), scanning transmission electron microscopy (STEM), and energy dispersive X-ray analysis (EDS). To the best of our knowledge, this is the first report analyzing the BSA-AuNCs by CW-EPR/LEPR technique. Besides the presence of Au(0) and Au(I) oxidation states in BSA-AuNCs, the authors observe a significant amount of Au(II), which may result from a disproportionation event occurring within NCs: 2Au(I) → Au(II) + Au(0). Based on the LEPR experiments, and by comparing the behavior of BSA versus BSA-AuNCs under UV light irradiation (at 325 nm) during light off-on-off cycles, any energy and/or charge transfer event occurring between BSA and AuNCs during photoexcitation can be excluded. According to CW-EPR results, the Au nano assemblies within BSA-AuNCs are estimated to contain 6–8 Au units per fluorescent cluster. Direct observation of BSA-AuNCs by STEM and HR-TEM techniques confirms the presence of such diameters of gold nanoclusters in BSA-AuNCs. Moreover, in situ formation and migration of Au nanostructures are observed and evidenced after application of either a focused electron beam from HR-TEM, or an X-ray from EDS experiments.